The Post and Electronic Communications Regulatory Authority : reading in tasks and powers under the law 18-04 - Bouldjedri, Ridha; Salmi, Wadra (Journal of Human Sciences, 2023)
This research aims to clarify the importance of Law 18-04, which defines the general rules relating to mail and electronic communications, through which we have approached some of the powers and competences, organizational and regulatory of the Authority of regulation of the Post and Electronic Communications within the market، within the face of the competitive mentality between the economic concessionaires on the one hand and the interests of the consumers on the other hand.